Antibodies detectable by counterimmunoelectrophoresis against Bacteroides antigens in serum of patients with inflammatory bowel disease. - Helphingstine, C J (1979)
Heat-extracted antigens from seven species of Bacteroides were used in passive hemagglutination and counterimmunoelectrophoretic tests. Sera from 87 normal persons (group I) and 15 patients with ulcerative colitis (group II) were of low and equal reactivity in passive hemagglutination tests; all positive tests were eliminated by 2-mercaptoethanol reduction of the sera. When these same sera were tested by counterimmunoelectrophoresis with six of the Bacteroides antigens, no significant difference in the percentage of positive reactions was noted. However, using the chi-square test, the seventh antigen, prepared from Bacteroides vulgatus, successfully distinguished the two populations at the 0.025 level. Counterimmunoelectrophoretic tests with the B. vulgatus antigen also provided a means to separate the patients in group II with active disease from those in remission at a P value of 0.01. All the sera from 12 patients with defined Crohn's disease activity indexes reacted with the B. vulgatus antigen in counterimmunoelectrophoretic tests. Reduction and alkylation of patient sera with 2-mercaptoethanol and iodoacetamide removed detectable antibody in 78% of the samples, which suggested a dominant role of immunoglobulin M in the response to Bacteroides antigens.